2006
DOI: 10.2527/2006.841229x
|View full text |Cite
|
Sign up to set email alerts
|

Application of broken-line analysis to assess floor space requirements of nursery and grower-finisher pigs expressed on an allometric basis1

Abstract: Few issues in swine production are as complex as floor space allowances. One method for pork producers to calculate floor space allowance (A) is to convert BW into a 2-dimensional concept yielding an expression of A = k * BW(0.667). Data on ADG, ADFI, and G:F were obtained from published peer-reviewed studies. Five data sets were created: A = grower-finisher pigs, fully slatted floors, and consistent group size; B = grower-finisher pigs and fully slatted floors (group size did not need to be consistent); C = g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
155
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(167 citation statements)
references
References 19 publications
6
155
2
1
Order By: Relevance
“…In the case of slatted floors, the proportion of variance explained by the quadratic and the broken-line regressions are the same (r 2 5 0.32); nevertheless, the threshold k 0 -value (0.039 6 0.002) obtained with the broken-line regression is relatively higher than the value of 0.032 to 0.035 found by Gonyou et al (2006) for an optimal performance of growing-finishing pigs housed either on partially or totally slatted floors. This would indicate that the expression of lying behaviour as space availability decreases may be compromised before a reduced performance becomes apparent.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In the case of slatted floors, the proportion of variance explained by the quadratic and the broken-line regressions are the same (r 2 5 0.32); nevertheless, the threshold k 0 -value (0.039 6 0.002) obtained with the broken-line regression is relatively higher than the value of 0.032 to 0.035 found by Gonyou et al (2006) for an optimal performance of growing-finishing pigs housed either on partially or totally slatted floors. This would indicate that the expression of lying behaviour as space availability decreases may be compromised before a reduced performance becomes apparent.…”
Section: Discussionmentioning
confidence: 79%
“…In this sense, the use of broken-line regression analysis has proven to be a valuable tool in the determination of critical values when studying the effect of different characteristics of pig-housing environment on their physiology and behaviour (Huynh et al, 2005a and2005b;Aarnink et al, 2006). Broken-line analysis has been also successfully used in the determination of the critical floor space allowance for pigs' performance (Gonyou et al, 2006), suggesting that it might also be helpful in attempting to determine a critical space allowance value affecting the average time growing-finishing pigs spend lying. As the behaviour of pigs is directly related to the floor space provided, Gonyou et al (2006) suggested that consistency of behaviour over the range of weights studied should be sought, if any attempt to quantify the relationship between behaviour and space allowance was to be carried out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study showed that pigs are able to adapt their feeding strategy according to the group size, although the effect of group size on pigs' performance is rather limited (Turner et al, 2003). The flooring characteristics are also known to modulate the effect of physical space, temperature or housing enrichment on pigs' excretory, lying and investigative behaviours (Aarnink et al, 2006;Averó s et al, 2010a and2010b), as well as their performance (Gonyou et al, 2006). Nevertheless, the simultaneous and interactive effects of all these influences have not been estimated.…”
Section: Introductionmentioning
confidence: 99%